The Effects of Context and Attention on Spiking Activity in Human Early Visual Cortex - Self, Matthew W.; Peters, Judith C.; Possel, Jessy K.; Reithler, Joel; Goebel, Rainer; Ris, Peterjan; Jeurissen, Danique; Reddy, Leila; Claus, Steven; Baayen, Johannes C.; Roelfsema, Pieter R. (PLOS Biology, 2016)
Quantitative analysis of spiking activity of neurons in area V2/V3 of the human visual cortex shows remarkable similarities to the response properties of neurons in the early visual cortex of the macaque monkey, justifying extrapolation between species.